2018
DOI: 10.1038/s41371-018-0029-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum immunoglobulin levels to blood pressure and hypertension in an adult population

Abstract: Evidence suggests long-term chronic inflammation, as the pathological basis of formation and development, plays an important part in atherosclerosis. Immunoglobulins (Igs) provided key information on the humoral immune status. However, few studies have evaluated the correlation between Igs and hypertension and blood pressure (BP) in a general population. We designed a cross-sectional study to evaluate whether serum Ig levels are related to BP and the prevalence of hypertension. About 12,373 participants in Tia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…Four studies described the association of cardio-metabolic risk factors (blood pressure and anthropometric measures such as weight and BMI) with serum immunoglobulin levels ( 6 , 18 , 56 , 111 ). Although different definitions of high blood pressure were applied ( Supplementary Table S2 ), high compared to normal blood pressure was generally associated with higher IgA and IgG levels ( 6 , 111 ) and no difference in IgM levels ( 6 , 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies described the association of cardio-metabolic risk factors (blood pressure and anthropometric measures such as weight and BMI) with serum immunoglobulin levels ( 6 , 18 , 56 , 111 ). Although different definitions of high blood pressure were applied ( Supplementary Table S2 ), high compared to normal blood pressure was generally associated with higher IgA and IgG levels ( 6 , 111 ) and no difference in IgM levels ( 6 , 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is now evident that hypertension is an inflammatory disease, with key roles played by most innate and adaptive immune cells, including DCs, monocytes/macrophages, γδ T cells, CD4 + T helper cells, CD8 + cytotoxic T cells, and B cells (7). Modest elevations of serum Igs have also been observed in both experimental and human hypertension (24,25), but whether hypertension is associated with a GC reaction is not known. Here we show that genetic or pharmacological inhibition of IL-21 results in blunted hypertension and reduced vascular inflammation/dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma patients complicated with rhinitis, whether allergic or non-allergic, or airway infections could lead to elevation of total IgE levels because of chronic in ammation and the reactivity of IgE against microorganisms [27][28][29][30]. In addition to infection, air pollutants such as diesel exhaust particles can also impair the integrity of airway epithelium, which promotes in ltration of pathogens via the damaged epithelium, causing in ammation responses [31].Regarding other conditions such as COPD, EGPA, type II diabetes, CVDs and hypertension, studies have also observed up-regulated levels of serum total IgE in these diseases [32][33][34][35][36]. However, whether these diseases could affect total IgE levels remains unclear and the underlining mechanism of IgE overproduction in nonatopic asthma requires further investigation.…”
Section: Discussionmentioning
confidence: 99%